Municipal Corporation of Greater Mumbai coat-of-arms - Ghosh, Ayan (2023)
Brihanmumbai Municipal Corporation (BMC), also known as Municipal Corporation of Greater Mumbai or Bombay Municipal Corporation, is India's richest municipal corporation and is responsible for developing and maintaining the civic infrastructure of the city and tax collection. It was established with the passing of the Bombay Municipal Corporation Act in 1888. The headquarters are based at the BMC building which also features (along with the Gateway of India) on the seal of the corporation.